A gynandromorph of the stonefly Amphinemura zonata (Okamoto, 1922) (Plecoptera: Nemouridae) from Japan - Hanada, Satoko; Yamamoto, Eiji (Zootaxa, 2023)
A gynandromorph of Amphinemura zonata (Okamoto, 1922) collected from Matsubara-izumi Pond in Japan is described and illustrated as the first report in the genus. The specimen exhibits bilateral gynandromorphism on abdominal sterna 7–9 and the paraprocts. Male features occur on the right half and female features on the left half. In addition, the gynandromorph is predominantly female as it retains female features on the dorsal male half of the abdomen, has eggs in the abdomen, has female-length fore wings, and lacks main male features such as an epiproct and a hypoproct on sternum 9.